Rational Versus Adaptive Expectations in Present Value Models - Chow, Gregory C. (The Review of Economics and Statistics, 1989)
Using data on stock price and dividends, and on long-term and short-term interest rates, the authors test an important implication of present value models–that current value is a linear function of the conditional expectations of the next-period value and the current determining variable . This implication, combined with rational expectations, is strongly rejected. Combined with adaptive expectations, it is accepted. The latter model can also explain the observed negative relation between the rate of return and stock price. Thus the rational expectations assumption should be used with caution; the adaptive expectations assumption may be useful in econometric practice. Copyright 1989 by MIT Press.(This abstract was borrowed from another version of this item.)